2022
DOI: 10.3390/genes13122307
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Polymorphisms of SMAD1, SMAD2 and SMAD3 Genes and Their Association with Litter Size in Tibetan Sheep (Ovis aries)

Abstract: SMAD1, SMAD2, and SMAD3 are important transcription factors downstream of the TGF-β/SMAD signaling pathway that mediates several physiological processes. In the current study, we used cloning sequencing, RT-qPCR, bioinformatics methods and iMLDR technology to clone the coding region of Tibetan sheep genes, analyze the protein structure and detect the tissue expression characteristics of Tibetan sheep genes, and detect the polymorphisms of 433 Tibetan sheep and analyze their correlation with litter size. The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…SMAD2 mediates various physiological processes and is a significant candidate for influencing litter size traits in Tibetan sheep. Genes can be used as molecular genetic markers to assist in selecting improved reproductive characteristics in the initial stages of sheep breeding (Li et al, 2022). Maintaining the survival of dilated oocytes through SMAD2 improves the fertilization and subsequent development of closed oocytes during oocyte-oocyte complex (COC) maturation, thereby enhancing maternal reproductive performance (Wu et al, 2021).…”
Section: Reproduction-related Genesmentioning
confidence: 99%
“…SMAD2 mediates various physiological processes and is a significant candidate for influencing litter size traits in Tibetan sheep. Genes can be used as molecular genetic markers to assist in selecting improved reproductive characteristics in the initial stages of sheep breeding (Li et al, 2022). Maintaining the survival of dilated oocytes through SMAD2 improves the fertilization and subsequent development of closed oocytes during oocyte-oocyte complex (COC) maturation, thereby enhancing maternal reproductive performance (Wu et al, 2021).…”
Section: Reproduction-related Genesmentioning
confidence: 99%
“…SMAD2 is a member of the SMAD protein family, a key intermediary in transforming growth factor beta (TGF-β) signaling [ 45 ], which plays a vital role in mammary gland development [ 46 ]. Notably, evidence showed that SMAD2 was associated with goat growth traits [ 47 ], sheep litter size [ 48 ], and buffalo milk yield traits [ 49 ]. In addition, SMG1 belongs to the phosphatidylinositol 3-kinase-related kinase (PIKK) protein family, triggering the activation of AMPK, which aids in the regulation of milk production and mammary gland biology [ 50 ].…”
Section: Discussionmentioning
confidence: 99%